2009
DOI: 10.1007/s11581-009-0313-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ceramic electrolytic films by the method of solution aerosol thermolysis (SAT) for solid oxide fuel cells (SOFC)

Abstract: The technique of solution aerosol thermolysis (SAT) for the production of ceramic electrolytic films suitable for solid oxide fuels cells was investigated. The research has focused on the optimization of process parameters and characterization of the obtained films by means of X-ray diffractometry and scanning electron microscopy/energy-dispersive spectroscopy. Dense films of gadolinia-stabilized ceria of uniform thickness have been successfully produced on substrates consisting of dense disks of yttria-stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
5
13
0
Order By: Relevance
“…after decomposition of the salts) would be very advantageous for film formation since particles are very reactive after thermolysis and their small pore and crystallite sizes as well as high purity constitute all the necessary prerequisites for a low temperature sintering process. 20 In all types of films, the sintering temperatures required to obtain the crystalline phase was 700 • C which is in agreement with previous work on ceramic films by Papastergiades et al 9 XRD diffractograms for CuO-CeO 2 and CuO-LSCM are shown in Figures 2 and 3 respectively along with standard XRDs of constituent materials. It can be seen that no additional phases are present after sintering.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…after decomposition of the salts) would be very advantageous for film formation since particles are very reactive after thermolysis and their small pore and crystallite sizes as well as high purity constitute all the necessary prerequisites for a low temperature sintering process. 20 In all types of films, the sintering temperatures required to obtain the crystalline phase was 700 • C which is in agreement with previous work on ceramic films by Papastergiades et al 9 XRD diffractograms for CuO-CeO 2 and CuO-LSCM are shown in Figures 2 and 3 respectively along with standard XRDs of constituent materials. It can be seen that no additional phases are present after sintering.…”
Section: Resultssupporting
confidence: 89%
“…Another advantage lies in their potential of producing nanocomposite electrodes that offer enhanced electrochemical performance. 8 The spray pyrolysis (SP) technique belongs to this family of deposition methods 9 and involves spraying of a solution of metal salts onto a heated substrate. Its use and versatility for fabrication of nanostructured materials was pointed out by Schoonman almost two decades ago.…”
mentioning
confidence: 99%
“…The solubility of CeA decrease with increasing temperature from 115 g/L at 15 1C to 100 g/L at 25 1C [25], whereas the solubilities of CeN and CeAN increase with increasing temperature from 637 g/L at 25 1C to 739 g/L at 50 1C [26] for CeN and from 1409 g/L at 25 1C to 2268 g/L at 85.6 1C [27] for CeAN. In addition, the melting temperatures of cerium nitrate hydrate, cerium ammonium nitrate and cerium acetate hydrate are 60 1C [19], 108 1C [28] and 300 1C [14], respectively. Due to the high solubility of CeAN and CeN salts, they should undergo volume precipitation to generate solid particles [16].…”
Section: Resultsmentioning
confidence: 99%
“…1(a), obtained from TGA data with the temperature ranges of $ 50 to $ 110 1C, $ 110 to $ 160 1C, $ 160 to $ 280 1C and $ 280 to $ 800 1C are attributed to formation of Ce( [17] and CeO 2 (53% of CeA), which are in agreement with the calculated weightloss values of 97%, 92%, 63% and 50%; the endothermic peak of 158 1C and the exothermic peaks of 201 1C and 250 1C shown in the DTA data suggest dehydration and the formation of cerium complexes of oxyacetate (Ce(OH)(CH 3-COO)) and dioxocarbonate (Ce 2 O 2 CO 3 ) [17,18], respectively. For CeN, TGA shows that only two weight-loss stages of $ 50 to $ 230 1C and $ 230 to $ 800 1C are associated with dehydration of CeN (Ce(NO 3 ) 3 ) and the formation of CeO 2 [19] as shown in Fig. 1(b).…”
Section: Methodsmentioning
confidence: 97%
“…In general, nitrate hydrates have lower melting points than those of acetate hydrates (Messing et al, 1993). For example, the melting temperatures of cerium nitrate hydrate and cerium acetate hydrate are 60°C (Papastergiades et al, 2009) and 300°C (Chen et al, 2008 b ), respectively. So, cerium nitrate hydrate melts before water is completely removed, and the molten salt will inhibit the removal of the entrapped water.…”
Section: Resultsmentioning
confidence: 99%